Gaining insight into the photophysical properties of a coumarin STP ester with potential for bioconjugation - González-Pérez, M. (2019)
Coumarins have a long history as fluorescent dyes.1 These benzopyrones are widely distributed in nature and new ones are continuously being synthesized and commercialized due to their excellent light stability and the relative ease in tuning their photophysical properties by chemical substitution.2–4 Coumarins that favor reactions of interest with target biomolecules, metals or reactive groups have been extensively exploited as fluorescent labels3–8 (e.g. coumarins containing amine reactive moieties, sulfotetrafluorophenyl (STP) or N-hydroxysuccinimide (NHS) esters are efficient dyes for biolabeling of molecules containing primary amine groups).2,9–11